On the definition of genre - Kalinauskaitė, Danguolė (Taikomoji kalbotyra, 2014)
Text genres fall within the scope of interest of text linguistics. However, genre studies are not limited to this branch of linguistics, because the methods appropriated for this kind of studies vary to a large extent. An in-depth linguistic study of texts and their language inevitably goes beyond the limits of a few branches of linguistics: it combines the theory of semantics, pragmatics and text linguistics, including their methods. Moreover, corpus linguistics seems to be of specific importance in this kind of studies, including both the diachronic and synchronic aspects of study.Some researchers treat text genre linguistics as a separate branch of linguistics (see Heinemann 2000, Gansel 2011). The present paper suggests that the understanding of genre should not be limited to a certain set of textual conventions; it could be treated as a meaningful communicative action. In this context, genre recognition by informants seems to be of paramount importance. This approach to the genre, including the invocation of genre recognition, is fundamental in arguing that any texts, even short ones, could be analyzed as independent and produced under certain genre rules identified in the texts. The author of this paper adheres to the view that text units meaningful in communication and functioning without reference to other texts should be regarded as independent texts. Texts meaningful in communication refer to those conveying information, emotions, attitudes, etc., i. e. the addressers of such texts communicate with their addressees, and the latter perceive and recognise such texts as an expression of certain communicative situations. This paper discusses headlines in the news portals as one of the objects of independent text studies to substantiate the theoretical foundation introduced in the paper. It also presents the results of a pilot survey carried out to identify how internet users perceive headlines in the news portals. The results of the survey suggest that headlines in the news portals could be perceived as texts with a communicative purpose and the means to achieve it. Therefore headlines could be treated as characterized by certain attributes that help identify them as specific texts.